(untitled) (Bangladesh Journal of Agricultural Research, 2014)
The paper has studied the economic viability of improved technology (Introduced under NAIP component-3) for extraction of cashew kernel from cashew nut in Bastar region of Chhattisgarh, India. Cost concept has been used to calculate economics of cashew kernel. The technology (Boiling, steaming, cutting, drying, and peeling) has been found viable over conventional practices (Traditional manual separation by stone or hammer) on account of higher recovery of 40 percent and cost reduction by 29.71 percent. Overall net profit per unit (One unit includes one boiler, one steamer, two cutter, one dryer, six peelers and cost of land, depreciation and interest on working capital) in the case of improved technology has been estimated to be Rs 7.32 lakh. Cost of production in machine extraction practices was 202.80 Rupees per kilogram of cashew in spite of traditionally practiced 288.56 Rupees per kilogram. The cost benefit ratio was found higher in machine extraction (1.57) as compare to traditionally practiced (0.169). The mechanical decortications and separation could not only save time and money, also reduced women drudgery (due to manual breaking by stone or hammer to separate kernel). The technology has been found suitable for promotion of entrepreneurship on the processing of cashew kernel from cashew nut in the production catchments which otherwise is not properly utilized. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20166 Bangladesh J. Agril. Res. 39(1): 165-172, March 2014